The haunted waters of Congo in Alain Mabanckou’s Lumières de Pointe-Noire (2013) and Petit Piment (2015) - Pagano, Adelaide (Oltreoceano - Rivista sulle migrazioni, 2024)
Lumière de Pointe-Noire (2013), an autobiographical story, and the picaresque novel Petit Piment (2015), whose protagonist is an orphaned child who wanders the labyrinthine streets of Pointe-Noire. Both texts evoke the legend of Mami Watta, who is both a maternal and sensual mermaid, and a deadly spirit. This ancient mythical creature haunts the seas along with other magical spirits and is part of Congolese beliefs. In Lumière de Pointe-Noire, the aquatic space, evoked through Mabanckou’s memories, remains forbidden to children’s games because of its magic effect on men. The author plunges us into a sinister affair, in which the sea is the murderous protagonist, by using photographs, which enrich the reading, and cinematographic art, whose references are scattered throughout the story. The writer describes the prohibitions and the popular legends imposed on him as a child and the fear of the ocean, while taking a critical look at these popular legends as an adult. Similarly, the myth of the mermaid and the dangers of the sea are recounted in his picaresque novel, Petit Piment: here the creature is a murderous figure who captures the orphans and drags them into the abyss of the waters. The author uses fiction to ironically denounce the educational system and popular beliefs. In this way, Mabanckou elaborates on his childhood memories associated with the ocean and filters these beliefs through the naive eyes of the little orphan, which enables the superposition of the author-child with his protagonist. Finally, the character of Doukou Daka, Petit Piment’s teacher, emerges from the narrative as a positive figure, who embodies the voice of reason, comparable to the adult author of Lumière de Pointe-Noire.